Status and Causes of Soil Salinization of Irrigated Agricultural Lands in Southern Baja California, Mexico - Tsuneyoshi Endo; Sadahiro Yamamoto; Juan A. Larrinaga; Hideyasu Fujiyama; Toshimasa Honna (Applied and Environmental Soil Science)
Selected farmlands in southern Baja California, Mexico, were surveyed to determine the levels and the causes of salinization/sodication in irrigated agricultural soil. The salt dynamics observed in profiles differed from farm to farm. Low EC and high pH levels were observed in the profiles of sandy fields, because the salt composition of these soils can easily change when salts are leached by irrigation water that contains carbonates of sodium. On the other hand, high levels of salinity and sodicity were observed in the soils of clayey fields. Soil salinization/sodication is complexly interrelated with soil characteristics, the amount and composition of salts in the soil, the quantity and quality of irrigation water applied, and the irrigation methods used. Our findings indicate that irrigation water in Baja California should be supplied at a rate that is sufficient to meet crop requirements without exacerbating salt accumulation.